Occurrence of Candida albicans in Periodontitis - Brahim Jabri; Maryem Iken; Mohamed Achmit; Sana Rida; Oum Keltoum Ennibi (International Journal of Dentistry)
Background. Periodontal diseases are the result of an imbalance between the microbiota and immune defense. The role of yeast in the pathogenesis of these diseases has been studied. This study aims to assess the occurrence of Candida albicans in periodontitis. Materials and Methods. Fifty subjects were recruited for the study (15 healthy individuals and 35 periodontitis subjects). The periodontal examination and plaque sampling were carried out for all patients. Candida albicans identification was based on culture, direct examination, and polymerase chain reaction. The statistical analysis was performed by SPSS 20 (SPSS Inc., Chicago, IL, USA). Results. Twenty percent of the diseased group harbored Candida albicans which was slightly higher than in the healthy group (7%), suggesting that, under normal conditions, yeast does not grow easily in subgingival sites. However, no significant difference between the healthy and periodontitis groups (p=0.23) was found. Our results also indicated that the presence of Candida albicans was neither gender nor age related in the studied groups. Conclusion. The results of this study suggest that Candida albicans occurs in periodontitis. More studies are needed to clarify the potential role of this yeast in different stages and forms of the disease.